A method for measuring glycerol-blanked triglyceride concentrations by using gas chromatography-isotope dilution mass spectrometry. (May 2020) - Koyama, Isao; Imano, Hironori; Nakamura, Masakazu; Kitamura, Akihiko; Kiyama, Masahiko; Miyamoto, Yoshihiro; Iso, Hiroyasu
Background: Serum triglyceride concentrations are measured as total glycerides content in many Western countries. In Japan, glycerol-blanked triglycerides (TG-GB) are measured to identify postprandial hypertriglyceridaemia and to minimize the influence of glycerol formulation on serum triglyceride values. However, TG-GB measurements have not been standardized. Therefore, we developed an efficient quantification system for total glycerides and free glycerol that allows the calculation of TG-GB concentrations. Methods: We measured total glycerides and free glycerol in human serum by using gas chromatography-isotope dilution mass spectrometry and compared its performance to the reference method of the US Centers for Disease Control and Prevention (CDC). Results: Our practical method of total glycerides and free glycerol quantification achieved excellent precision for both within-run and among-run coefficients of variation (<1.5% and <2.7%, respectively), with an average recovery of 99.8% for free glycerol. However, we noted an average %bias of –0.26% for total glycerides and –3.15% for free glycerol between our TG-GB method and the CDC reference method. Conclusions: This practical method of total glycerides and free glycerol quantification enables traceability assessment of TG-GB measurements. Differences between the output values of TG-GB and the CDC reference method might result from the differences in free glycerol values.